MEMPERKENALKAN TEKNOLOGI KOMPUTER PADA ANAK - Marlina Marlina (Universitas Bina Sarana Informatika, 2012)
The development of computer technology is now growing rapidly. Many of the jobs or activitiesundertaken by adults and children using computer technology. However, many parents worryabout their children when using computers. Parents are worried about a computer can make thechild isolated from his friends so much time spent alone regardless of the circumstances. As wellas many other negative influences that parents feared would happen to their children if theyintroduce computers to children early age. Be aware if the parents actually introduce computers tochildren accompained by prudent supervison will actually gained alot of positif impact. Onepositive effect obtained is to improve learning ability and skills of chiledren. In order to obtainoptoimal benefit that a parent or teacher can choose a program that fits the child prossessed theinteligence level of inteligence so that it can stimulate them with educational or edutainmentprograms.Keywords: computer introduces tips, Impact of computers, tips on choosing a computer program